Digital Educational Games to Improve Numerical Literacy of Elementary School Students - Yonanda, Devi Afriyuni; Saputra, Dudu Suhandi; Rofi’i, Agus; Rosidah, Ani; Febriyanto, Budi (Yayasan Gema Bina Nusantara, 2025)
This study was motivated by the low results of the first grade students' beginning reading skills. The purpose of this study was to determine the effect of mobile applications on beginning reading skills in grade I SDN Bonang 1 Panyingkiran District, Majalengka Regency, West Java Province. The research method used was quasi experiment. The samples in this study were grade IA students and grade IB students of SDN Bonang 1 in the 2024/2025 school year with research subjects as many as 20 experimental class students and 20 control class students determined through purposive sampling. Data collection techniques in this study were through student beginning reading skills tests. This study uses quantitative data analysis techniques on pretest and posttest data. The results of the analysis showed that there was a significant difference in beginning reading skills between students who learned using mobile applications and students who learned using textbooks. The conclusion is proven by the Independent Sample T-test which shows a significance value of 0.022 which is smaller than the significance value limit of 0.05. Based on the data obtained, the use of mobile applications has a greater impact than the use of textbooks. This means that students who learn with mobile apps have better beginning reading skills compared to students who learn with textbooks.